Health threats of climate change: from intersectional analysis to justice-based radicalism - Ghosh, Aditya; Dutta, Kaberi (Ecology and society, 2024)
Intersectional impacts of climatic changes are producing unforeseen physical and mental health challenges such as acute depression, stress, severe malnutrition, cervical cancer, sexually transmitted diseases for the poor and marginalized women and children. Conducted in the Indian Sundarbans, a social-ecological system critically stressed by climate change, this study disentangles, uncovers, and highlights obscured ways in which sudden and slow-onset eco-climatic shifts induced by climatic changes interact with existing patterns of social-ecological (mis)governance, gender inequity, power structures and struggles, therein, patriarchal policies and neoliberal markets. Coping mechanisms of the communities are shaped by complex, multi-layered, and scalar processes that involve institutional failures, private markets, and neoliberal governance patterns, which in turn are resulting in severely negative health consequences for women and children. Employing a justice lens and an agent-based coproduction of knowledge helps to move beyond the obscured causalities for specific health threats to foster an agenda for action. At the local scale, this framework identifies diverse and novel ways in which development policies and governance across domains must synergize to enhance specific capacities of women and children, allowing them to make right adaptation choices that bolster their long-term resilience. Theoretically, it uncovers how the global resilience agenda is increasingly being dominated by disaster capitalism that is producing negative health consequences at the local levels. Private capital, in conjunction with or through alliances with the state, identify weaknesses of resilience governance as profiteering opportunities and promote “adaptation” products and services through a hegemonic process. Despite producing maladaptation in the Sundarbans, the hegemony ensures that the pattern is reinstated and reproduced consensually. This pushed the responsibility of maladaptation into individual domains. Repoliticizing and affirmatively sabotaging this resilience design seems essential, which future studies should aim for.
Gesehen am 14.10.2024